AD/ART dan Bisnis Plan sebagai Penguatan Kelembagaan Bank Sampah Induk Pelangi Siak Sri Indrapura - Jeni Wardi; Alexsander Yandra; Junaidi; Latifa Siswati; Ambar Tri Ratnaningsih (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Recent developments related to Bank Sampah Induk Pelangi (BSIP) after receiving assistance from the waste bank program from Chevron and UNILAK, there has been an increase in activities and more effective governance. In this program, the Bank Sampah Induk Pelangi has received equipment/tools assistance to capacity building. Capacity Building that has been provided in the first year, namely training on composting fertilizer for the management of the Bank Sampah Induk Pelangi and Waste Bank Unit, training on making paving blocks from plastic waste, Occupational Health and Safety Training, training on product packaging and online marketing, and training on the use and maintenance of machines. machine operators, both press and chopper. But in its journey, the Bank Sampah Induk Pelangi still has problems in terms of unclear organizational structures, job descriptions, unprofessionalism, and the sustainability of the Waste Bank's business and business. human capacity building and institutional strengthening of the rainbow parent waste bank, namely training on making basic budgets/household budgets and waste bank business plans. This training uses the method of presenting material on the preparation of the basic budget/household budget and the waste bank business plan as well as the practical and simulation method of making the basic budget/household budget and the waste bank business plan. The result of this training is that the management of the Bank Sampah Induk Pelangi has been able to draft the articles of association and bylaws and business plans, so that the management of the waste bank already understands the benefits of the articles of association and by-laws and business plans. Besides that, the management of the Rainbow Main Waste Bank also understands matters relating to the importance of a business plan for the sustainability of the waste bank in the future.